Stereoselective Synthesis of Drugs and Natural Products 2013
DOI: 10.1002/9781118596784.ssd011
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Conjugate Addition in Stereoselective Synthesis

Abstract: Conjugate addition is a privileged method in organic synthesis allowing for the formation of new CC bonds, molecules that can serve as valuable synthons for total synthesis. It is highly attractive thanks to the presence of at least one functional group on the Michael partners, a group that can be easily derivatized. In this field, organocatalyzed reactions have recently changed the way of thinking about synthetic approaches, notably, as soon as carbonyl groups are involved. As a result, numerous applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…In order to optimize atom efficiency, we reverted to 1 equiv of 5 and added a catalytic quantity of 18-crown-6 to activate the enolate, which led to an increased yield without loss of diastereoselectivity (entry 7). In the literature it has been observed that adding crown ethers in catalytic quantities enhances the reactivity of enolates to alkylation by complexing the sodium ion . Optimum conditions were obtained by portionwise addition of sodium hydride to provide a low concentration of free base and afforded cyclopentane 7 in both excellent yield and selectivity (85%, 9:1 dr , entry 8).…”
mentioning
confidence: 99%
“…In order to optimize atom efficiency, we reverted to 1 equiv of 5 and added a catalytic quantity of 18-crown-6 to activate the enolate, which led to an increased yield without loss of diastereoselectivity (entry 7). In the literature it has been observed that adding crown ethers in catalytic quantities enhances the reactivity of enolates to alkylation by complexing the sodium ion . Optimum conditions were obtained by portionwise addition of sodium hydride to provide a low concentration of free base and afforded cyclopentane 7 in both excellent yield and selectivity (85%, 9:1 dr , entry 8).…”
mentioning
confidence: 99%